The role of link workers in weight management for people with severe mental illness: a qualitative study - Rija Imran; Alexandra Kenny; Geoffrey Wong; Charlotte Lee (BMC Primary Care)
Abstract Background People with severe mental illness (SMI) have an increased risk of cardiovascular disease, partly due to factors such as overweight and obesity. Weight management programmes can potentially reduce this risk, but people with SMI face barriers to access and engagement. Aim To explore the acceptability of using link workers to address barriers to accessing and engaging with weight management programmes for people with SMI. Design and Setting A qualitative study conducted with people with SMI, link workers, and health promotion workers in primary care. The study was co-designed and co-delivered with a person with lived experience of SMI. Method Five online focus groups and dyad interviews were run with 13 participants, including seven people with SMI and six health professionals (three link workers and three health promotion workers), between 25 July 2023 and 31 March 2024. Discussions were audio-recorded, transcribed verbatim, and analysed using a codebook thematic analysis in NVivo software. Results We constructed three analytical themes. (1) The view of link workers: all participants saw link workers as valuable in overcoming emotional and practical barriers to weight management. (2) Expectations of link worker support: support must be personalised, culturally responsive, and focused on building trust. (3) Challenges for link workers: barriers included limited mental health training, undefined roles, and capacity concerns. Conclusion Link workers offer an acceptable, low-intense approach to improving access to weight management programmes for people with SMI. Strengthening coordination between link workers and weight management services in primary care, as well as defining their role and level of support, could improve outcomes for this underserved group.